Naskah-Naskah Keislaman Pandalungan: Islamic Manuscripts of Pandalungan - Muhammad Ardiansyah (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2015)
This paper is more of a report on preservation, conservation, and reconstruction activities of Islamic intellectual heritage through the inventory of manuscripts found in the Pandalungan region. This is important given the discovery of many manuscripts in poor and neglected conditions. The manuscripts themselves have yet to be explored in terms of their content and historical dimensions. The content and historical dimensions of these manuscripts can provide valuable information and knowledge for historiographical studies and the social history of Islamic intellectualism in the Pandalungan region. This initiative is an initial effort to prepare a database of Islamic manuscripts in Pandalungan, which can be used as a basis for further research on the intellectual heritage of Indonesian Islam, particularly in Pandalungan. Thus, these manuscripts will remain readable and alive as dynamic entities within communities that continue to evolve. The study of these manuscripts is also expected to reconstruct the intellectual heritage and social history of past societies. Through these manuscripts, we hope to write the social history and intellectual traditions of Pandalungan Islam from an